Navigating the Digital Frontier: Strategies for Effective Risk Management in Islamic Banking - Susanto, Rosya Mawaddah (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to analyze effective approaches and strategies in digital risk management in Islamic banking, with a focus on risk identification, implementation of policies and procedures, use of technology, employee education and training, audit and monitoring, collaboration with external parties , and commitment. leader. This research method involves a literature review from academic and industry sources related to digital risk management in Islamic banking. The research results show that a holistic approach that includes a deep understanding of digital risks, effective implementation of policies and procedures, use of advanced technology, employee education and training, continuous auditing and monitoring, collaboration with external parties, and strong commitment from leaders, is key in managing digital risk in Islamic banking. Practical suggestions include increasing investment in security technology and strengthening cooperation with external parties to strengthen defenses against digital risks.